Peran Etika dalam Menjaga Integritas dan Kepercayaan Publik terhadap Industri Perbankan di Indonesia - Farah Qalbia; M. Reza Saputra (Pusat Riset dan Inovasi Nasional, 2023)
Ethics in the banking industry plays a crucial role in maintaining integrity and public trust. This study aims to explore the role of ethics in preventing violations that could damage the stability of the financial system and the reputation of banks. Using a qualitative approach, this research employs case studies and literature reviews to analyze various cases of ethical violations in the Indonesian banking industry. The findings reveal that strong professional ethics can reduce the risk of fraud and moral hazard among bankers. However, challenges such as weak oversight and profit pressures remain significant factors influencing ethical breaches. Implementing sound corporate governance principles, enhancing ethics education, and tighter regulatory oversight are considered essential to strengthening banking ethics. This study concludes that by reinforcing commitment to ethics, the banking industry can increase public trust and support sustainable economic growth.